Caminos de frontera: Espacio y poder en la historia del piedemonte Amazónico colombiano (2019)
Objective/context: This article analyzes of ethnographic, geographical and cartographic discourses around transportation infrastructure plans and projects in the Andean-Amazonian foothills of southern Colombia. Specifically, it shows how the colonial and postcolonial vision of the foothills as a physical and symbolic frontier between a “civilized” and a “savage” world has been instrumental in the conception and execution of such plans and projects, and, more broadly, in the control and appropriation of the Amazonian region. Originality: Usually, historical works on the Colombian nation-building have adopted a monolithic and centric vision of infrastructure because development has historically been confined to a limited portion of the national territory. On the contrary, this article focuses on the role of regions considered “frontiers”, “peripheries” or “margins” in the construction and legitimation of a hegemonic state project. Methodology: The research is based on the analysis and contrasting of primary sources such as travelers’ accounts, cartographic representations, and missionary and government archives. Conclusions: By establishing historical continuity in the discourses and infrastructure practices of the Andean-Amazonian foothills, we can conclude that these are part of a long-standing tradition in which the foothills is seen as a frontier, and roads and highways are viewed as “civilizing” infrastructure of the Amazonian space. © 2019, Universidad de los Andes, Bogota Colombia. All rights reserved.